Driving public support for a meat tax: Fiscal policies and behavioral interventions - Ainslee Erhard; Sanchayan Banerjee; Meike Morren (Georg-August University of Göttingen, RTG 2654 Sustainable Food Systems, 2024)
Taxing meat optimally is a first-best policy outcome to internalize environmental harms. However, meat taxes often lack public and governmental support. Recent research indicates that support for meat taxes can be improved by combining behavioral nudges with fiscal measures. In this study, we test this claim in a preregistered between-within-subjects experiment using a representative sample of the Dutch (N=2,032) population. The Netherlands is currently considering a meat tax legislation, thereby making our study timely and policy relevant. Participants were randomly assigned to a treatment condition in a 2x2 experimental setup, varying across a framing nudge ("tax" versus "levy") and a reflection ("yes" versus "no") dimension. Subsequently, all participants engaged in a discrete choice experiment where they selected their preferred meat pricing policy from six sets of choice cards. Each card included random variations in levels of four attributes: meat pricing (costs), revenue recycling, policy coverage, and pricing rationale. We find that policy support increases with greater revenue recycling and broader policy coverage but decreases as costs rise. The rationale behind pricing does not alter public support substantially. Importantly, we find no significant difference in public support across the different behavioral nudge or reflection treatments. Our experimental findings underscore the importance of policy design in enhancing support for meat taxes. The effective design of a meat tax is crucial, as superficial changes, such as behavioral nudges, may not be sufficient to sway public opinion.
Keywords: 330; Meat tax; Framing nudge; Public support